(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Family background influences young education and job opportunities, affecting social and economic inclusion. Youth from disadvantaged families face an increased risk of being NEET and a high risk of labour or social marginalization. An analysis of Chilean data examined gender disparities in the impact of familiar households lacking education, occupation, and social protection from 5D-multidimensional poverty measures on the likelihood of being NEET among youth aged 20-29. Using Propensity-Score Matching to account for selection bias, the average treatment effect on the population and the treated group were estimated. In the raw sample, 23.1% of young people aged 20-29 were NEETs, increasing with age and women experiencing higher rates. Results showed that the population average effect of households lacking occupation-unemployment- in both genders have a significantly higher risk of being NEET than those without this deprivation.Conversely, living in a household lacking social protection significantly reduces this risk, especially in young women.A small effect of households lacking schooling on the probability of being NEET in both genders was observed, but only significant in men. Future research should include panel data to explore youth life trajectories to assist policymakers in preventing social exclusion and marginalization of young people.